2017
DOI: 10.1007/s10753-017-0720-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Respiratory Syncytial Virus Toll-Like Receptor 3-Mediated Immune Response with COPD Exacerbation Frequency

Abstract: The objective of the study is to explore the role of respiratory syncytial virus Toll-like receptor 3 (TLR3)-mediated immune response in the pathogenesis of acute exacerbations of chronic obstructive pulmonary disease (AECOPD). A total of 20 AECOPD patients and 10 normal volunteers were studied. TLR3 was detected by RT-PCR, and respiratory syncytial virus (RSV) was detected by nested RT-PCR. Then, A549 cells were infected by RSV at different time points and at different viral titers. TLR3 mRNA was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…37,38 Respiratory viral infections and responses of TLR3 also cause airway inflammation that is associated with exacerbations in patients with COPD. 4,13,39 The present study revealed a clinical role of lnc-IL7R in modulating the TLR response, the impairment of which contributes to augmented inflammation in COPD.…”
Section: Discussionmentioning
confidence: 60%
“…37,38 Respiratory viral infections and responses of TLR3 also cause airway inflammation that is associated with exacerbations in patients with COPD. 4,13,39 The present study revealed a clinical role of lnc-IL7R in modulating the TLR response, the impairment of which contributes to augmented inflammation in COPD.…”
Section: Discussionmentioning
confidence: 60%
“…Mechanistic data demonstrates that RSV infection promotes P. aeruginosa-mediated biofilm formation [92]. In vitro data show that A549 cells show increased expression of TLR3 following RSV infection [53]. This leads to increased NF-kB activity and IL-8 release [54].…”
Section: Respiratory Syncytial Virus In Copdmentioning
confidence: 99%
“…More recently, FOOTITT et al [52] demonstrated increased indices of oxidative and nitrosative stress and impaired macrophage activity (histone deacetylase, HDAC2) following HRV infection in COPD. The toll-like receptor (TLR)-3 pathway signalling may be implicated in RSV-induced exacerbation [53,54]. Several studies suggest that viral infection is associated with more frequent and more severe exacerbations [42,44,55].…”
Section: Mechanisms Of Virus-induced Copd Exacerbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a white matter injury (WMI) model, TLR3 was colocalized with the ER and autophagosome in ventral lateral posterior neurons, indicating that autophagy could be regulated by TLR3 (Vontell et al, 2015 ). Since TLR3 also participated in the process of inflammation (Liu et al, 2018 ), so whether inhibiton of TLR3 could suppress TBI-induced inflammation by modulation of autophagy was unclear, which required further researches.…”
Section: The Regulation Molecules Of Autophagy In Tbimentioning
confidence: 99%